DUKUNGAN KELOMPOK TANI DUKUNGAN KELOMPOK TANI TERHADAP PERILAKU PETANI PADI ORGANIK DALAM BUDIDAYA YANG RAMAH LINGKUNGAN: PERILAKU PETANI PADI ORGANIK DALAM BUDIDAYA YANG RAMAH LINGKUNGAN - Kordiyana K Rangga; Listiana, Indah; Safitri, Anggun (Politeknik Negeri Lampung., 2024)
This study aims to determine the level of behavior of organic rice farmers in carrying out environmentally friendly rice cultivation, the relationship between farmer group support and other factors related to the behavior of organic rice farmers in carrying out environmentally friendly rice cultivation in Purwo Kencono Village, East Lampung. This research was conducted in Purwo Kencono Village, Sekampung Udik District, East Lampung Regency in October 2022. The respondents in this study were members of the Multi Baliwo farmer group with 30 people in total This study uses the census method with a descriptive-quantitative approach using data testing using non-parametric statistics using Spearman's Rank correlation test. The results showed that the behavior level of organic rice farmers was in the medium category. In this study, there are four factors that influence the behavior of farmers, namely: age, education level, and length of farming, but the results of the Spearman Rank correlation test show that only farmer group support is related to the behavior of organic rice farmers in carrying out environmentally friendly rice cultivation with a significance value of 0.487. ** which means the correlation strength is quite strong. Farmer groups have tried to maximize their role for organic rice farmers, especially in improving the behavior of organic rice farmers in carrying out environmentally friendly rice cultivation